Diskursif Tokoh Kabul dalam Novel Orang-Orang Proyek melalui Pendekatan Studi Wacana Kritis Bourdieu - Sahrul Romadhon; Anas Ahmadi; Budinuryanta Yohanes; Faizal Hadi Nugroho (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to find anticorruption values in the novel Orang-Orang Proyek (OOP) by Ahmad Tohari. The anti-corruption values analyzed refer to three main elements of anti-corruption attitudes, namely (a) core: honesty, discipline, and responsibility; (b) attitude: fairness, courage, and caring; and (c) work ethic: hard work, simplicity, and independence. These three elements are reflected through the character of the main character in the novel, Kabul, who faces various moral dilemmas and pressures in the world of construnction projects full of corrupt practices. The research method used is qualitative with a grounded theory approach. This approach allows the generalization of postmodern critical discourse theory and Pierre Bourdieu's cultural sociology to understand the power relations and social structures that shape the anti-corruption narrative in the novel. The results show that anti-corruption values in the novel Orang-Orang Proyek are reflected through the behavior and life principles of the main character who consistently rejects involvement in corrupt practices, despite facing great personal risks. The findings also emphasize the importance of moral education through literature, especially to instill an anti-corruption culture from an early age. Thus, the results of this study can be a practical recommendation in the development of character education curriculum among students. The introduction of anti-corruption values through literature is expected to build a generation with integrity and critical awareness of the dangers of corruption in everyday life.